Responding with resilience: the impact of the pandemic on the educational experiences and ambitions on FE students. (30th April 2022) - Raven, Neil
Concerns have been expressed about the impact of Covid-19 on the educational ambitions and progression prospects of those from disadvantaged backgrounds. While the pandemic has limited opportunities to conduct research in this area, approaches can be developed that overcome the barriers of conducting fieldwork in person. This article reports on the interim findings from one such study. This sought the views of students on advanced (Level 3) programmes at a further education college with a catchment area comprising a number of low higher education (HE) participation neighbourhoods. While lockdown had presented challenges for participants in engaging with their education and in planning for their next steps, all expressed a determination to succeed and achieve their ambitions. The article concludes by suggesting a key role for outreach in helping these students realise their post-college goals.